2022
DOI: 10.1111/jocs.16369
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary prevalence and outcomes of rheumatic mitral valve surgery

Abstract: Objective: Rheumatic mitral valve disease is often viewed as a historic disease in North America with limited contemporary data. We hypothesized that rheumatic pathology remains common and has worse short-term outcomes and higher resource utilization compared to other mitral valve pathologies.Method: All patients undergoing mitral valve repair or replacement (2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019) were extracted from a regional Society of Thoracic Surgeons database. Resource utilization metrics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 23 publications
0
12
1
Order By: Relevance
“…2 Although no differences in operative mortality or morbidity were discerned, patients with RHD required longer hospital and intensive care lengths-of-stay. 2 The authors should be congratulated for their compelling study which reminds us that RHD is a disease of inequity and reflects how immigrant, Indigenous, racialized, and lowsocioeconomic status (SES) populations still face barriers to accessing healthcare. Lack of primary care results in delayed treatment for GAS and acute rheumatic fever and thus a greater likelihood of developing RHD that progresses into mitral valve failure requiring surgical intervention.…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…2 Although no differences in operative mortality or morbidity were discerned, patients with RHD required longer hospital and intensive care lengths-of-stay. 2 The authors should be congratulated for their compelling study which reminds us that RHD is a disease of inequity and reflects how immigrant, Indigenous, racialized, and lowsocioeconomic status (SES) populations still face barriers to accessing healthcare. Lack of primary care results in delayed treatment for GAS and acute rheumatic fever and thus a greater likelihood of developing RHD that progresses into mitral valve failure requiring surgical intervention.…”
mentioning
confidence: 90%
“…Hawkins et al 2 conducted a retrospective cohort study in the United States and found that the proportion of RHD amongst all mitral valvular diseases was 12.6% and increased by 0.39%/year from 2011 to 2019. 2 Although no differences in operative mortality or morbidity were discerned, patients with RHD required longer hospital and intensive care lengths-of-stay. 2 The authors should be congratulated for their compelling study which reminds us that RHD is a disease of inequity and reflects how immigrant, Indigenous, racialized, and lowsocioeconomic status (SES) populations still face barriers to accessing healthcare.…”
mentioning
confidence: 99%
See 3 more Smart Citations